Strain-Divergent m6A Landscapes Modulate Nipah Virus Replication and METTL3 Inhibition Attenuates Virulence - Ting Luo; Zhen Chen; Fang Zhang; Haibin Liu; Fang Huang; Xueyan Zhang; Jiangpeng Feng; Shuang Ding; Lishi Liu; Wuxiang Guan; Aiping Zeng; Haojie Hao (Viruses)
Nipah virus (NiV), a highly lethal zoonotic paramyxovirus, displays strain-specific pathogenicity, yet the molecular basis for this divergence remains elusive. Here, we identify N6-methyladenosine (m6A) modification as a pivotal regulator of NiV replication. Higher m6A methylation levels on viral genomic RNA and mRNAs are associated with the increased virulence observed in the NiV-Malaysia (NiV-M) strain compared to NiV-Bangladesh (NiV-B). Underlying this phenomenon, NiV infection orchestrates a reprogramming of the host m6A machinery by downregulating the methyltransferase METTL3 and the demethylase ALKBH5, while concurrently upregulating m6A reader proteins YTHDF1-3. Both METTL3 and ALKBH5 bind directly to NiV RNA, with METTL3 installing m6A to promote viral replication and ALKBH5 removing them to inhibit it. Strikingly, pharmacological inhibition of m6A modification markedly attenuates NiV replication in vitro and in vivo, underscoring the therapeutic potential of targeting the m6A pathway. Our study establishes m6A as a key determinant of NiV pathogenicity and provides a paradigm for host-directed antiviral strategies against high-risk RNA viruses.